1979
DOI: 10.1159/000117671
|View full text |Cite
|
Sign up to set email alerts
|

HL-A Antigens and the Response to Prophylactic Lithium

Abstract: 82 consecutive patients checked at the out-patient clinic of the Psychiatric Department of the Umeå University were typed for HL-A antigens. The patients belonged to the diagnostic subgroups: bipolar (manic-depressive) psychosis (n = 33), unipolar recurrent depressive psychosis (n = 29) and cycloid psychosis (n = 20) and all had been on lithium treatment for at least 6 months. By comparing the group of those who did not relapse on lithium therapy (n = 48) with the group of those who did relapse (n = 34) there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In 1979, Perris et al . found that the frequency of HLA‐A3 antigen was significantly higher in lithium non‐responders 59 . This relationship between HLA‐A3 antigen and non‐response to prophylactic treatment by lithium was confirmed by other researchers 7,60 , 61 .…”
Section: Human Leukocyte Antigen Typingsupporting
confidence: 68%
“…In 1979, Perris et al . found that the frequency of HLA‐A3 antigen was significantly higher in lithium non‐responders 59 . This relationship between HLA‐A3 antigen and non‐response to prophylactic treatment by lithium was confirmed by other researchers 7,60 , 61 .…”
Section: Human Leukocyte Antigen Typingsupporting
confidence: 68%
“…Differences in cellular HLA surface protein composition between BPD patients who respond well to lithium and non-responders were first reported over 30 years ago in several studies. These reports noted that leukocyte HLA-A3 antigen reactivity was reported to be associated with poor lithium response, whereas the absence of HLA-A3 predicted a favorable response [58][59][60] . At the same time, in vitro experiments suggested that lithium binds to HLA antigens on cultured human leukocytes 61 .…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher frequency of the HLA-A3 antigen among patients who re lapsed on lithium prophylaxis has been re ported by Perris et al [1979b], who also observed that patients with the B18 antigen were all non-responders to treatment.…”
Section: Introductionmentioning
confidence: 86%